BAGAIMANA DEWAN PENGAWAS SYARIAH MELAKUKAN PENGAWASAN OPERASIONAL BANK? - Sepky Mardian; Aulia Putri Oktaviani Justri; Nida Faradila; Nur Hidayah Fitriani; Ufairoh Muti’ah; Zakia Mardhotillah (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten, 2020)
This study aims to find out how the Sharia Supervisory Board (DPS) conducts operational supervision of banks. This study uses a qualitative approach based on primary data in the form of interviews with DPS in one of Indonesia's sharia banks and is also a member of the National Sharia Council-Indonesian Ulema Council (DSN-MUI). The analysis was carried out by compiling interview transcripts with key information and providing analysis based on regulations and literature studies. The results and discussion in this study prove that in practice, it is confirmed that what is done by DPS is shari'a review not shari'ah audit. The review process and mechanism carried out refer to the guidelines and provisions issued by DSN-MUI and the Financial Services Authority.